The Hubungan Pola Makan, Aktivitas Fisik, dan Tingkat Stres dengan Kejadian Hipertensi pada Ibu Hamil di Kelurahan Talang Putri Kota Palembang - Rista Silvana; Ratika Febriani; Yuni Fitrianti; Hasyifa Khaila Rahmawaty (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension in pregnancy remains an important maternal health problem because it contributes to maternal morbidity and mortality. This study aimed to analyze the association of dietary pattern, physical activity, and stress level with the incidence of hypertension among pregnant women in Talang Putri Subdistrict, Palembang City. A quantitative study with a case-control design was conducted. The sample consisted of 78 respondents, including 26 cases and 52 controls, selected by simple random sampling from third-trimester pregnant women recorded in 2025 and 2026. Data were collected through interviews using a modified food frequency questionnaire, the 2018 Riskesdas physical activity instrument, and the Depression Anxiety Stress Scale for stress assessment. Bivariate analysis used the chi-square test at a 5% significance level and odds ratio estimation. The results showed that dietary pattern was significantly associated with hypertension in pregnancy (p=0.000; OR=12.4). Physical activity was also significantly associated with hypertension (p=0.032; OR=3.07). Similarly, stress level had a significant association with hypertension (p=0.000; OR=11.4). In conclusion, poor dietary pattern, heavy physical activity, and severe stress were associated with hypertension among pregnant women. These findings highlight the need for nutrition education, physical activity regulation, and stress management in antenatal care.